2000
DOI: 10.1104/pp.124.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Induces the ADP-Glucose Pyrophosphorylase Gene,ApL3, and Starch Synthesis in Arabidopsis

Abstract: In Arabidopsis, genes encoding functional enzymes for the synthesis and degradation of trehalose have been detected recently. In this study we analyzed how trehalose affects the metabolism and development of Arabidopsis seedlings. Exogenously applied trehalose (25 mm) strongly reduced the elongation of the roots and, concomitantly, induced a strong accumulation of starch in the shoots, whereas the contents of soluble sugars were not increased. When Arabidopsis seedlings were grown on trehalose plus sucrose (Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
144
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 56 publications
11
144
0
4
Order By: Relevance
“…Coordinated sugar transcriptional regulation of several starch biosynthetic genes has been suggested by numerous works (19). Induction of several ADP-Glc PPase-encoding genes has been reported in different species including Arabidopsis (16,(25)(26)(27)(28). We show that, under physiological conditions, only two ADP-Glc PPaseencoding genes, ApL3 and ApL4, are controlled by sugars (Figs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Coordinated sugar transcriptional regulation of several starch biosynthetic genes has been suggested by numerous works (19). Induction of several ADP-Glc PPase-encoding genes has been reported in different species including Arabidopsis (16,(25)(26)(27)(28). We show that, under physiological conditions, only two ADP-Glc PPaseencoding genes, ApL3 and ApL4, are controlled by sugars (Figs.…”
Section: Discussionsupporting
confidence: 66%
“…5), suggesting that different signaling pathways may be involved in the transcriptional control of ApL3 and ApL4 by sugars. To date, trehalose-regulated expression of ApL3 has been shown (28), but no data regarding ApL4 regulation have been published. Trehalose feeding rescues the phenotype of the adg2-1 mutant lacking ApL1 (17), and it was proposed that under these conditions, APL3 would substitute for APL1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al (2011) suggested that TPS11 provides a threshold level of 'signaling' trehalose that is essential for regulating Arabidopsis defense against GPA, including the up-regulation of PAD4 expression and full extent of starch accumulation. Trehalose application promotes starch accumulation in Arabidopsis leaves (Wingler et al, 2000;Kolbe et al, 2005;Singh et al, 2011). As shown in other studies, the ability of trehalose to promote starch accumulation in GPAinfested plants could be due to the inhibition of starch turnover (Ramon et al, 2007) and/or the redox activation of AGPase, a key enzyme in starch synthesis, by trehalose-6-phosphate (Paul et al, 2008).…”
Section: Tps11 and Trehalosementioning
confidence: 63%
“…Trehalose has been shown to stabilize dehydrated enzymes, proteins and lipid membranes efficiently, as well as protect biological structures from damage during desiccation. In the plant kingdom, most species do not seem to accumulate detectable amounts of trehalose, with the exception of highly desiccation-tolerant resurrection plant, Selaginella lepidophylla (Wingler, 2002). In bacteria and yeast, trehalose is synthesized in a two-step process: trehalose-6-phosphate is first formed from UDP-glucose and glucose-6-phosphate in a reaction catalyzed by trehalose-6-phosphate synthase (TPS).…”
Section: Targeting Osmotic Homeostasis Machinerymentioning
confidence: 99%